+0  
 
0
42
2
avatar+182 

Simplify the Complex Expression:

(8-√-11) (8+√-11)

 

I keep on getting 76, even though I know the answer is 75. If someone could explain what I'm doing wrong, I'd appreciate that. Thank you.

Here's my work:

 

(8-√-11) (8+√-11)

= (8-i√11) (8+i√11)

= (64 - i+11)

= 75 - i2

= 75 - (-1)

= 75 + 1

=76

 May 15, 2020
 #1
avatar+142 
+1

the problem is your 3rd step
 

(8-i√11) (8+i√11) = 
64 - i2(11)

that should get you 75

 

 May 15, 2020
 #2
avatar+182 
0

Thank you. I understand what I did wrong. 

auxiarc  May 15, 2020

22 Online Users

avatar
avatar
avatar